EDEN ISS - Vrakking, Vincent; Philpot, Claudia; Schubert, Daniel; Zabel, Paul; Zeidler, Conrad; Dorn, Markus; Bunchek, Jess; Ferl, Robert; Paul, Anna-Lisa (2023)
Ant-Land Status Report describing activities and preliminary results of the 2022 Antarctic winter season and the 2022/23 Antarctic summer season